Mutations in the HFE gene (C282Y, H63D, S65C) in a Brazilian population - Bueno,Simone (2006)
Hereditary hemochromatosis (HH) is the most common genetic disorder occurring in individuals of northern European descent. The clinical characteristic of this disease is the gradual accumulation of iron in internal organs, which ultimately leads to organ failure and death. The defective gene in the majority of cases, HFE, was identified in 1996. Three allelic variants of the HFE gene have been correlated with HH: C282Y is significantly associated with HH; H63D and S65C have unclear relationships. In this report, these mutations were analyzed in 8 patients with HH and in 148 healthy individuals (blood donors). To detect the mutations, exons 2 and 4 of the HFE gene were amplified by PCR followed by restriction endonucleases cleavage. In patients with HH, three individuals were homozygous for the C282Y mutation, one showed compound heterozygous (C282Y/H63D), one was heterozygous for the C282Y and 3 presented with no mutations. In healthy individuals, the allele frequency observed was 0.014 for C282Y, 0.108 for H63D and 0.010 for S65C. The frequency of mutations was significantly higher in Caucasians compared with non-Caucasians. These data are concordant with the previous literature and with the ethnical origin of the population studied.